Penning-trap experiments for spectroscopy of highly-charged ions at HITRAP - Vogel, Michael; Andelkovic, Z.; Birkl, G.; Ebrahimi, S.; Hannen, V.; Lindenfels, David-Friedrich von; Martin, A.; Murböck, T.; Nörtershäuser, W.; Quint, W.; Schmidt, S.; Segal, D. M.; et al. (Physica scripta, 2015)
Highly charged ions offer the possibility to measure electronic fine structures and hyperfine structures with precisions of optical lasers. Microwave spectroscopy of transitions between Zeeman substates further yields magnetic moments (g-factors) of bound electrons, making tests of calculations in the framework of bound-state QED possible in the strong-field regime. We present the SPECTRAP and ARTEMIS experiments, which are currently being commissioned with highly charged ions in the framework of the HITRAP facility at GSI, Germany. We present the scientific outline, the experimental setups and first results with confined ions.
Gesehen am 25.06.2020